ANALISIS KESULITAN BELAJAR KIMIA PADA MATERI LARUTAN PENYANGGA SISWA KELAS XI IPA 1 MAN 2 PONTIANAK - Rita Dwi Purnama; Mawardi Mawardi; Raudhatul Fadhilah (Jurnal Ilmiah Ar-Razi, 2016)
ABSTRACTThe low students’ learning outcomes and the failure in achieving the maximum mastery standard in Buffer Solutions material are caused by the students’ inability in understanding the questions. Students tend to merely pay attention on the Buffer Solutions material when the learning process takes place. However, they face confusion when they have to answer the questions of the task and the test. This study aimed at discovering the difficulties and the factors related to the students’ difficulties on Buffer Solutions material at XI IPA 1 class of MAN 2 Pontianak. Using case study descriptive method and qualitative approach, this study employed 29 students as the samples. The data collection technique used were indirect communication (questionnaires), direct communication (interview), and documentation techniques. While the data collection tools used were achievement test, questionnaires and interview. The data analysis results indicated that 68.3% students had difficulties on pH and pOH Buffer Solutions. On the other hand, the internal factorsthat affected the student learning difficulties were motivation aspect, that is, the students 'attention to the Buffer Solutions (54.31%), and talent aspect that influenced the student’s learning difficulties, that is, the students’ ability in recognizing numbers and figures respectively (48,6%) and talent aspect that influenced the student’s learning difficulties in Buffer Solutions materials (47%). In addition, the external factor that affected the student learning difficulties were family as the place to study (56%), and school as the facilitator (56,56%). Thereby, students are expected to further enhance the knowledge on the Buffer Solutions and have a discussion with both teachers and peers to cope with their learning difficulties.Keywords: Analysis, Students’ Learning Difficulties, Buffer Solutions